2020
DOI: 10.1186/s12870-020-2276-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects and interaction of soybean maturity gene alleles controlling flowering time, maturity, and adaptation in tropical environments

Abstract: Background: Soybean is native to the temperate zones of East Asia. Poor yields of soybean in West African countries may be partially attributed to inadequate adaptation of soybean to tropical environments. Adaptation will require knowledge of the effects of allelic combinations of major maturity genes (E1, E2, and E3) and stem architecture. The long juvenile trait (J) influences soybean flowering time in short,~12 h days, which characterize tropical latitudes. Soybean plant architecture includes determinate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
2
12
0
1
Order By: Relevance
“…During amplification, it was found that the e6 lines did not produce a band for exons 3 and 4 (Fig. 2 b) similar to the non-amplification reported by Miranda et al ( 2020 ). By using TaKaRa LA Taq®, an unexpected ~10,000 bp band was produced in the new amplicons for the last 2 exons of the gene in the e6 lines, while a ~1500 bp band was seen for the wild type lines (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…During amplification, it was found that the e6 lines did not produce a band for exons 3 and 4 (Fig. 2 b) similar to the non-amplification reported by Miranda et al ( 2020 ). By using TaKaRa LA Taq®, an unexpected ~10,000 bp band was produced in the new amplicons for the last 2 exons of the gene in the e6 lines, while a ~1500 bp band was seen for the wild type lines (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study described a lack of amplification at the J locus in Paranagoiana and labeled it as the j−x allele. However, the study did not differentiate between both J and E6 loci (Miranda et al 2020 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The present study mainly focused on identifying new long juvenile genotypes and verifying whether the J mutations are associated with delayed flowering in soybean. The long juvenile genetic mechanism in most tropical genotypes especially Sub-Sahara Africa is not known (Miranda et al 2020). Huaxia 3, the check variety, was introduced to some African countries and resulted in an increased productivity (Yue et al 2017).…”
Section: Association Of the Haplotypes With The Phenotypic Traitsmentioning
confidence: 99%